Relationship Between Family Function And Psychological Well-Being Among Caregiver Of Schizophrenia Patients In Menur Mental Hospital Jawa Timur - Dya Sustrami; Dewa Ayu Indira Wardhani; Ari Susanti; Abdul Habib (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
Background: Families often get burdened by the behavioral and emotional changes of schizophrenic patients. This burden is impacting family functions. The function of the family as a caregiver for people with schizophrenia includes problem-solving, communication, roles in the family, affective responses, behavioral control, and general family functions. Disturbed family functions can increase the burden on the caregiver; this has an impact on the psychological well- being of the family caregiver. Purpose: Analyzing the relationship between family function and psychological well-being among caregiver of schizophrenia patients in Menur Mental Hospital Jawa Timur. Methods: This study used the Analytical Observational design with a Cross-Sectional approach with a population of 264 respondents from families who nursed their family members with schizophrenia. The sampling technique used was Simple Random Sampling and used 160 samples that met the inclusion criteria. This study used the Family Assessment Device (FAD) and the Ryff Psychological Wellbeing Scale (RPWS) questionnaire, and data analysis used the Spearman Rho Correlation Test with a significance of (?<0.05). Result: The results showed that most of the family functions were in the high category, with 86 respondents (53.8%), and most of the psychological well- being was also in the high category, with 75 respondents (46.9%). Statistical tests that used the Spearman Rho test obtained the results of = 0.012, which means the correlation results are very low. Conclusion: This shows that the value of 0.05 indicates a connection between family functions and the psychological well-being of caregivers of schizophrenia patients at Menur Psychiatric Hospital, East Java Provincial Government. Based on the study’s results, family functions and psychological well-being significantly affect the patient’s recovery.